MASSACHUSETTS TAX CAMPAIGN - DONAHUE T; SAVARESE J (Tufts Archival Research Center, 2007)
Memo from Savarese and Associates to Bob McAdam discussing the Masssachusetts tax campaign. Describes plan to gain organized labor as an ally in opposition to the proposed MA cigarette tax increase. Discusses meetings with labor and liberal leaders. Identifies labor's formal policy and goals. Aims to "translate labor's policy position into directed, concrete political action." Lists resources needed. Adresses political strategy, program elements, and media.